2018
DOI: 10.3920/bm2017.0029
|View full text |Cite
|
Sign up to set email alerts
|

The gut mycobiome composition is linked to carotid atherosclerosis

Abstract: The mycobiotic component of the microbiota comprises an integral, yet under-researched, part of the gastrointestinal tract. Here, we present a preliminary study of the possible contribution of gut mycobiota to sub-clinical atherosclerosis in a well-characterised group of obese and non-obese subjects in association with the Framingham Risk Score (FRS) and carotid intima-media thickness (cIMT). From all taxa identified, the relative abundance of the phylum Zygomycota, comprising the family Mucoraceae and genus M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 35 publications
1
34
0
1
Order By: Relevance
“…Another interesting observation was the positive association between the relative abundance of the genus Mucor and the subjects with normal Tg levels. This is in line with previous studies showing that Mucor is abundant in the gut of non-obese subjects [13], and confer protection from the risk of CVD [14]. In the present study, subjects stratified into NG and HG groups also differed in BMI levels (NG = 25.4±3.5; TG = 26.9±3.4 kg·m -2 ; p = 0.003), but no clustering between the gut mycobiome and BMI was observed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another interesting observation was the positive association between the relative abundance of the genus Mucor and the subjects with normal Tg levels. This is in line with previous studies showing that Mucor is abundant in the gut of non-obese subjects [13], and confer protection from the risk of CVD [14]. In the present study, subjects stratified into NG and HG groups also differed in BMI levels (NG = 25.4±3.5; TG = 26.9±3.4 kg·m -2 ; p = 0.003), but no clustering between the gut mycobiome and BMI was observed.…”
Section: Discussionsupporting
confidence: 93%
“…To date, research on the GM of elderly has focused on the bacterial component largely ignoring fungi, archaea and viruses [3], [10]. However, recent studies show that fungi have significant effects in the gut milieu despite their small proportion in number as compared to bacteria [11], and gut mycobiome dysbiosis has been associated with irritable bowel disease (IBD) [12], obesity [13], and carotid atherosclerosis vascular disease [14]. The fungal component of the gut microbiome of healthy individuals has been reported to be dominated by the yeast genera Saccharomyces, Malassezia , and Candida [15].…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Specific fungal composition could be potentially used to distinguish between obese and nonobese patients Diabetes (i) C. albicans is more prevalence in type 1 diabetes [123][124][125] (ii) C. albicans is more prevalence in type 1 and type 2 diabetes (iii) No difference is found between C. albicans colonization in type 1 and type 2 diabetes. [124] (iv) Isolated fungal species from type 1 diabetes patient is more resistant towards antifungal treatment [125] Atherosclerosis -(i) Phylum Zygomycota, which consists of family Mucoraceae and genus Mucor, was negatively correlated with the risk of cardiovascular disease development through carotid intima-media thickness (cIMT) method [129] Alcoholic liver disease -(i) Decreased in fungal diversity along with Candida overgrowth in alcohol-dependent patients [130] Central nervous system diseases Rett syndrome (i) High abundance of Candida genus were detected [134] Autism Spectrum disorder (i) Candida, Malassezia, Aspergillus, and Penicilliun genera were identified [135] Schizophrenia (i) Increased levels of S. cerevisiae and C. albicans species [136] (ii) Close association of gastrointestinal tract disturbance with elevation of C. albicans species and lower cognitive score [137] 7 Mediators of Inflammation role of gut fungi in different stages of colorectal adenoma. In the study, the authors characterized mucosal mycobiota in twenty-seven paired samples of adenomas and adjacent tissues, where Glomeromycota and Basidiomycota phyla dominated both adenomas and adjacent tissues from all subjects.…”
Section: Inflammatory Bowel Syndromes (Ibs)mentioning
confidence: 99%
“…Additionally, M. racemosus was the most prevalent species found in subjects with a low cardiovascular risk profile, and this species was negatively associated with FRS and cIMT. The authors suggest that M. racemosus could be a relevant biomarker for cardiovascular risk [129]. Thus, it seems that mycobiota could have its role in cardiovascular diseases and more studies are needed to unravel the beneficial effects of mycobiota in cardiometabolic diseases.…”
Section: Inflammatory Bowel Syndromes (Ibs)mentioning
confidence: 99%
“… Cani et al (2007) found that gut dysbiosis suppressed the expression of tight junction proteins, leading to an increase in intestinal permeability and subsequently the translocation of LPS into the blood ( Harris et al, 2012 ). Gut dysbiosis-derived LPS may play important roles by modulation of Toll-like receptors (TLRs) and their downstream targets ( Libby, 2002 ; Chacon et al, 2017 ). As part of the pattern-recognition receptors family, TLRs can recognize bacterial products and modulate the host immune system ( Akira and Takeda, 2004 ; Akira et al, 2006 ).…”
Section: Gut Microbiota and Atherosclerosismentioning
confidence: 99%